Asphalt-based sodium ion electrode hard carbon negative electrode material and preparation method thereof

By using a composite material of hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt, and a hard carbon anode material with excellent performance was prepared by ball milling and pyrolysis carbonization processes, the problem of poor performance of asphalt-based anode material in the prior art was solved.

CN119797333APending Publication Date: 2025-04-11ZHEJIANG WELLY ENERGY CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510099204.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The carbon-based anode of existing sodium ion batteries prepared by direct carbonization of asphalt have poor electrochemical performance, and the asphalt-based hard carbon anode materials on the market have a large gap with traditional hard carbon anode materials in terms of specific capacity and rate performance.

Method used

Using hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt as raw materials, the bituminous sodium ion electrode hard carbon anode material was prepared through ball milling treatment and pyrolysis carbonization process.

Benefits of technology

The specific capacity, Coulomb efficiency and cycle durability of the negative electrode material are significantly improved, and are better than conventional asphalt-based negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797333A_ABST
    Figure CN119797333A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to an asphalt-based sodium ion electrode hard carbon negative electrode material and a preparation method thereof. The preparation method comprises the following steps: step 1, preparing hafnium silicide powder; step 2, preparing hafnium silicide amp; cobalt selenide composite microspheres; step 3, performing amp treatment on hafnium silicide; mixing the cobalt selenide composite microspheres, reduced graphene oxide and asphalt, and performing ball milling treatment to obtain an asphalt-based mixture; and 4, placing the asphalt-based mixture in a graphite furnace, introducing nitrogen as a protective gas, carrying out heating treatment, and cooling to obtain the hard carbon negative electrode material. According to the invention, hafnium silicide amp is used; the sodium ion electrode hard carbon negative electrode material is prepared by taking sodium selenide, cobalt selenide composite microspheres, reduced graphene oxide and asphalt as raw materials, and the negative electrode material not only has excellent performance in the aspects of specific capacity and coulombic efficiency, but also has the advantage of long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to an asphalt-based sodium ion electrode hard carbon negative electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have the advantages of abundant resources, low cost, and environmental friendliness. They are considered to be one of the most likely to replace lithium-ion batteries and become one of the ideal power sources for large-scale energy storage applications. The performance of sodium-ion batteries is mainly determined by the sodium storage positive and negative electrode materials, and the sodium storage negative electrode material is an important component. Among the sodium storage negative electrode materials currently studied, the carbon-based negative electrode not only has a lower sodium insertion platform, higher capacity and good cycle stability, but also has the advantages of abundant resources and simple preparation. It is currently the most promising sodium storage negative electrode material. At present, the precursors used to prepare carbon materials are mainly biomass and resins. The carbon yield of biomass precursors is very low, and the cost of resin precursors is relatively high. As a by-product of the petroleum industry, asphalt has a low price and a high carbon yield, making it an ideal precursor for preparing carbon materials.

[0003] However, the electrochemical performance of the carbon-based negative electrode of sodium ion batteries prepared by direct carbonization of asphalt is very poor. This is because asphalt is a soft carbon precursor. During the direct carbonization of asphalt, aromatic hydrocarbons and alkanes are prone to polycondensation and rearrangement, resulting in a high degree of graphitization, small interlayer spacing, and few defect sites, resulting in poor sodium storage performance. Although its performance can be improved through some modification methods, the asphalt-based hard carbon negative electrode materials on the market still have a large gap with traditional hard carbon negative electrode materials in terms of specific capacity and rate performance. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide an asphalt-based sodium ion electrode hard carbon negative electrode material and a preparation method thereof.

[0005] The purpose of the present invention is achieved by the following technical solutions: In a first aspect, the present invention provides a method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material, comprising the following steps: Step 1, preparing hafnium silicide powder: Weigh silicon powder and hafnium powder, mix them, firstly ball-mill them under the protection of inert gas, then press them into tablets and place them in a graphite furnace for heating treatment to obtain hafnium silicide powder; Step 2, preparation of hafnium silicide & cobalt selenide composite microspheres: Cobalt acetate tetrahydrate, sodium selenite and deionized water are mixed, and hafnium silicide powder is added, and the mixture is stirred thoroughly to obtain a mixed solution A; ascorbic acid is weighed and dissolved in deionized water, and the mixture is stirred evenly to obtain a mixed solution B; the mixed solution A and the mixed solution B are mixed, and reacted in a reactor. After the reaction is completed, hafnium silicide & cobalt selenide composite microspheres are obtained; Step 3, preparing asphalt-based mixture: The hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt are mixed and ball-milled to obtain an asphalt-based mixture; Step 4, preparing negative electrode material: The asphalt-based mixture is placed in a graphite furnace, nitrogen is introduced as a protective gas, the temperature is increased, and after cooling, a hard carbon negative electrode material is obtained.

[0006] Preferably, in step 1, the purity of the silicon powder and the hafnium powder are both greater than 99%, and the particle size is 50±5 μm; the mass ratio of the hafnium powder to the silicon powder is 1.78:0.56-0.6.

[0007] Preferably, in step 1, the ball milling speed is 200-400 r / min, and the ball milling time is 5-10 h.

[0008] Preferably, in step 1, the temperature of the graphite furnace is 900-1300° C., and the processing time is 2-5 hours.

[0009] Preferably, in the mixed solution A in step 2, the mass ratio of hafnium silicide powder, cobalt acetate tetrahydrate, sodium selenite and deionized water is 1:0.25-0.5:0.17-0.34:15-25.

[0010] Preferably, in the mixed solution B in step 2, the mass ratio of ascorbic acid to deionized water is 0.3-0.5:10.

[0011] Preferably, in step 2, the mixed solution A and the mixed solution B are mixed by stirring the mixed solution A at 50-80° C. for 2-4 hours, then adding the mixed solution B dropwise, and continuing to stir for 0.5-1 hour after all the mixed solution B is added.

[0012] Preferably, in step 2, the mass ratio of mixed solution A to mixed solution B is 1:0.3-0.8.

[0013] Preferably, in step 2, the temperature of the reactor is 130-180° C., and the reaction time is 5-10 h.

[0014] Preferably, in step 3, the purity of the asphalt is ≥99%, the softening point is 250±5°C, the ash content is ≤0.2%, and the residual carbon value is ≥70%.

[0015] Preferably, in step 3, the purity of the reduced graphene oxide is ≥99%, the diameter of a single layer is 0.5-10 μm, and the carbon-oxygen ratio is 9.73-10.97.

[0016] Preferably, in step 3, the mass ratio of hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt is 0.2-2:0.1-1:10.

[0017] Preferably, in step 3, the ball milling speed is 250-450 r / min, and the ball milling time is 3-10 h.

[0018] Preferably, in step 4, the heating treatment method in the graphite furnace is: first heating to 250-300° C., keeping the temperature for 1-3 hours, then heating to 750-950° C., keeping the temperature for 1-3 hours.

[0019] In a second aspect, the present invention provides an asphalt-based sodium ion electrode hard carbon negative electrode material prepared by the above-mentioned preparation method.

[0020] The beneficial effects of the present invention are: 1. The present invention uses hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt as raw materials to prepare a sodium ion electrode hard carbon negative electrode material, which not only performs well in specific capacity and coulombic efficiency, but also has the advantage of long cycle life.

[0021] 2. Compared with conventional asphalt-based negative electrode materials, the present invention not only adds hafnium silicide & cobalt selenide composite microspheres and reduced graphene oxide as modified reinforcing materials, but also the treatment of asphalt includes a process of softening and coating first and then pyrolysis and carbonization, so that the prepared negative electrode material has a more obvious enhancement effect in terms of initial discharge specific capacity, coulombic efficiency and overall cycle durability.

[0022] 3. Hafnium silicide & cobalt selenide composite microspheres are products obtained by using hafnium silicide powder as the matrix and then reacting on its surface to generate cobalt selenide. When it is combined with graphene as a modifier and enhancer for negative electrode materials, it increases the degree of defects in negative electrode materials, which is Na + Provides more active sites, thereby enhancing the Na + adsorption stability and diffusion rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0024] Figure 1 This is a SEM schematic diagram of the asphalt-based sodium ion electrode hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0026] The present invention will be further described below in conjunction with the following examples.

[0027] Example 1: A method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material, comprising the following steps: Step 1, preparing hafnium silicide powder: Weigh silicon powder and hafnium powder with a purity of more than 99% and a particle size of 50±5 μm, mix them, the mass ratio of hafnium powder to silicon powder is 1.78:0.58, ball mill under inert gas protection, the ball milling speed is 300 r / min, the ball milling time is 8 h, after the ball milling, press the tablets and place them in a crucible, then place the crucible in a graphite furnace, introduce inert gas into the graphite furnace as a protective gas, heat it to 1100° C., keep it warm for 3 h, then cool it to room temperature with the furnace, crush it to 10±2 μm, and obtain hafnium silicide powder; Step 2, preparation of hafnium silicide & cobalt selenide composite microspheres: Cobalt acetate tetrahydrate, sodium selenite and deionized water are mixed, and then hafnium silicide powder is added, the mass ratio of hafnium silicide powder, cobalt acetate tetrahydrate, sodium selenite and deionized water is 1:0.37:0.25:20, and after sufficient stirring, a mixed solution A is obtained; ascorbic acid is weighed and dissolved in deionized water, the mass ratio of ascorbic acid to deionized water is 0.4:10, and after stirring evenly, a mixed solution B is obtained; after the mixed solution A is placed at 60° C. and stirred for 3 hours, the mixed solution B is added dropwise, the mass ratio of the mixed solution A to the mixed solution B is 1:0.5, and after all are added, stirring is continued for 0.5 hours, and then poured into a reactor, and the reactor is placed at 150° C. for 8 hours. After the reaction is completed, the solid particles are collected by filtration, washed with water at least three times, and dried to obtain hafnium silicide & cobalt selenide composite microspheres; Step 3, preparing asphalt-based mixture: Take asphalt (purity ≥ 99%, softening point 250 ± 5 ° C, ash content ≤ 0.2%, residual carbon value ≥ 70%) and reduced graphene oxide (purity ≥ 99%, single layer diameter 0.5-10 μm, carbon-oxygen ratio 9.89), mix hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt in a mass ratio of 1:0.6:10, and ball mill at a speed of 350 r / min for 8 hours. After the ball milling, an asphalt-based mixture is obtained; Step 4, preparing negative electrode material: The asphalt-based mixture product is placed in a graphite furnace, and nitrogen is introduced as a protective gas. The temperature is first raised to 200°C and kept warm for 2 hours, then raised to 850°C and kept warm for 2 hours, and then cooled to room temperature with the furnace to obtain a hard carbon negative electrode material.

[0028] Example 2: A method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material, comprising the following steps: Step 1, preparing hafnium silicide powder: Weigh silicon powder and hafnium powder with a purity of more than 99% and a particle size of 50±5 μm, mix them, the mass ratio of hafnium powder to silicon powder is 1.78:0.56, ball mill under inert gas protection, the ball milling speed is 200 r / min, the ball milling time is 5 h, after the ball milling, put them in a crucible after pressing, and then put the crucible in a graphite furnace, introduce inert gas into the graphite furnace as a protective gas, heat it to 900°C, keep it warm for 5 h, then cool it to room temperature with the furnace, crush it to 10±2 μm, and obtain hafnium silicide powder; Step 2, preparation of hafnium silicide & cobalt selenide composite microspheres: Cobalt acetate tetrahydrate, sodium selenite and deionized water are mixed, and then hafnium silicide powder is added, the mass ratio of hafnium silicide powder, cobalt acetate tetrahydrate, sodium selenite and deionized water is 1:0.25:0.17:15, and after sufficient stirring, a mixed solution A is obtained; ascorbic acid is weighed and dissolved in deionized water, the mass ratio of ascorbic acid to deionized water is 0.3:10, and after stirring evenly, a mixed solution B is obtained; after the mixed solution A is placed at 50° C. and stirred for 2 hours, the mixed solution B is added dropwise, the mass ratio of the mixed solution A to the mixed solution B is 1:0.3, and after all are added, stirring is continued for 0.5 hours, and then poured into a reactor, and the reactor is placed at 130° C. for 5 hours. After the reaction is completed, the solid particles are collected by filtration, washed with water at least three times, and dried to obtain hafnium silicide & cobalt selenide composite microspheres; Step 3, preparing asphalt-based mixture: Take asphalt with a purity of ≥99%, a softening point of 250±5°C, an ash content of ≤0.2%, and a residual carbon value of ≥70%; take reduced graphene oxide with a purity of ≥99%, a single-layer sheet diameter of 0.5-10μm, and a carbon-oxygen ratio of 9.89, mix hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt in a mass ratio of 0.5:0.5:10, and ball mill at a speed of 250r / min for 3h. After the ball milling is completed, an asphalt-based mixture is obtained; Step 4, preparing negative electrode material: The product was placed in a graphite furnace, nitrogen was introduced as a protective gas, the temperature was first raised to 180°C, and the temperature was kept for 3 hours, then the temperature was raised to 750°C, and the temperature was kept for 3 hours, and then the furnace was cooled to room temperature to obtain a hard carbon negative electrode material. Example 3: A method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material, comprising the following steps: Step 1, preparing hafnium silicide powder: Weigh silicon powder and hafnium powder with a purity of more than 99% and a particle size of 50±5 μm, mix them, the mass ratio of hafnium powder to silicon powder is 1.78:0.6, ball mill under inert gas protection, the ball milling speed is 400 r / min, the ball milling time is 10 h, after the ball milling, press the tablets and place them in a crucible, then place the crucible in a graphite furnace, introduce inert gas into the graphite furnace as a protective gas, heat to 1300° C., keep the temperature for 2 h, then cool to room temperature with the furnace, crush to 10±2 μm, and obtain hafnium silicide powder; Step 2, preparation of hafnium silicide & cobalt selenide composite microspheres: Cobalt acetate tetrahydrate, sodium selenite and deionized water are mixed, and then hafnium silicide powder is added, the mass ratio of hafnium silicide powder, cobalt acetate tetrahydrate, sodium selenite and deionized water is 1:0.5:0.34:25, and after sufficient stirring, a mixed solution A is obtained; ascorbic acid is weighed and dissolved in deionized water, the mass ratio of ascorbic acid to deionized water is 0.5:10, and after stirring evenly, a mixed solution B is obtained; after the mixed solution A is placed at 80° C. and stirred for 4 hours, the mixed solution B is added dropwise, the mass ratio of the mixed solution A to the mixed solution B is 1:0.8, and after all are added, stirring is continued for 1 hour, and then poured into a reactor, and the reactor is placed at 180° C. for 10 hours. After the reaction is completed, the solid particles are collected by filtration, washed with water at least three times, and dried to obtain hafnium silicide & cobalt selenide composite microspheres; Step 3, preparing asphalt-based mixture: Take asphalt with a purity of ≥99%, a softening point of 250±5°C, an ash content of ≤0.2%, and a residual carbon value of ≥70%; take reduced graphene oxide with a purity of ≥99%, a single-layer sheet diameter of 0.5-10μm, and a carbon-oxygen ratio of 9.89, mix hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt in a mass ratio of 1.2:0.8:10, and ball mill at a speed of 450r / min for 10h. After the ball milling is completed, an asphalt-based mixture is obtained; Step 4, preparing negative electrode material: The product was placed in a graphite furnace, nitrogen was introduced as a protective gas, the temperature was first raised to 220°C, and the temperature was kept for 1 hour, then the temperature was raised to 950°C, and the temperature was kept for 1 hour, and then the furnace was cooled to room temperature to obtain a hard carbon negative electrode material.

[0029] Comparative Example 1 A pitch-based sodium ion electrode hard carbon negative electrode material, which differs from the preparation method of Example 1 in that no hafnium silicide & cobalt selenide composite microspheres are added, and pitch and reduced graphene oxide are directly used as raw materials for preparation. Specifically: Step 1, preparing asphalt-based mixture: The reduced graphene oxide and asphalt were mixed in a mass ratio of 1.6:10, and ball-milled at a speed of 350 r / min for 8 h. After the ball-milling, an asphalt-based mixture was obtained; Step 2, preparing negative electrode materials: The asphalt-based mixture is placed in a graphite furnace, and nitrogen is introduced as a protective gas. The temperature is first raised to 200°C and kept warm for 2 hours, then raised to 850°C and kept warm for 2 hours, and then cooled to room temperature with the furnace to obtain a hard carbon negative electrode material.

[0030] Comparative Example 2 A pitch-based sodium ion electrode hard carbon negative electrode material, the difference from the preparation method of Example 1 is that the composite microspheres are replaced with cobalt selenide microspheres, and the rest is the same as Example 1. Specifically: Step 1, preparation of cobalt selenide microspheres: Cobalt acetate tetrahydrate, sodium selenite and deionized water are mixed, the mass ratio of cobalt acetate tetrahydrate, sodium selenite and deionized water is 0.37:0.25:20, and after sufficient stirring, a mixed solution A is obtained; ascorbic acid is weighed and dissolved in deionized water, the mass ratio of ascorbic acid to deionized water is 0.4:10, and after stirring evenly, a mixed solution B is obtained; after the mixed solution A is placed at 60° C. and stirred for 3 hours, the mixed solution B is added dropwise, the mass ratio of the mixed solution A to the mixed solution B is 1:0.5, and after all are added, stirring is continued for 0.5 hours, and then poured into a reactor, and the reactor is placed at 150° C. for 8 hours. After the reaction is completed, the solid particles are collected by filtration, washed with water at least three times, and dried to obtain cobalt selenide microspheres; Step 2, preparing asphalt-based mixture: Cobalt selenide microspheres, reduced graphene oxide and asphalt were mixed in a mass ratio of 1:0.6:10, and ball-milled at a speed of 350 r / min for 8 h. After the ball-milling, an asphalt-based mixture was obtained; Step 3, preparing negative electrode material: The asphalt-based mixture product is placed in a graphite furnace, and nitrogen is introduced as a protective gas. The temperature is first raised to 200°C and kept warm for 2 hours, then raised to 850°C and kept warm for 2 hours, and then cooled to room temperature with the furnace to obtain a hard carbon negative electrode material.

[0031] Comparative Example 3 A pitch-based sodium ion electrode hard carbon negative electrode material, the difference from the preparation method of Example 1 is that the composite microspheres are replaced with hafnium silicide powder, and the rest is the same as Example 1. Specifically: Step 1, preparing hafnium silicide powder: Weigh silicon powder and hafnium powder with a purity of more than 99% and a particle size of 50±5 μm, mix them, the mass ratio of hafnium powder to silicon powder is 1.78:0.58, ball mill under inert gas protection, the ball milling speed is 300 r / min, the ball milling time is 8 h, after the ball milling, press the tablets and place them in a crucible, then place the crucible in a graphite furnace, introduce inert gas into the graphite furnace as a protective gas, heat it to 1100° C., keep it warm for 3 h, then cool it to room temperature with the furnace, crush it to 10±2 μm, and obtain hafnium silicide powder; Step 2, preparing asphalt-based mixture: The hafnium silicide powder, reduced graphene oxide and asphalt were mixed in a mass ratio of 1:0.6:10, and ball-milled at a speed of 350 r / min for 8 h. After the ball-milling, an asphalt-based mixture was obtained; Step 3, preparing negative electrode material: The asphalt-based mixture product is placed in a graphite furnace, and nitrogen is introduced as a protective gas. The temperature is first raised to 200°C and kept warm for 2 hours, then raised to 850°C and kept warm for 2 hours, and then cooled to room temperature with the furnace to obtain a hard carbon negative electrode material.

[0032] Experimental testing The performance of the negative electrode materials prepared in Example 1 and Comparative Examples 1-3 was tested, and the specific testing standards were referred to GB / T 43114-2023. The test items included the first discharge specific capacity, the first coulomb efficiency, and the capacity retention rate after 200 cycles.

[0033] Among them, the negative electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention are used as the negative electrode of the button battery, the separator is a polyethylene-polypropylene (PE-PP) composite film with a thickness of 80 μm; the electrolyte is a 1 mol / L LiPF solution; the battery shell is CR2032; the counter electrode and the reference electrode are sodium metal sheets; a battery tester; the charge and discharge rate is 0.1C, and the voltage range is 0.005-1.5V.

[0034] The test results are shown in Table 1: Table 1 Test results of different negative electrode materials Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 First discharge specific capacity (mA·h / g) 428.9 355.7 395.3 410.6 First coulombic efficiency (%) 93.5 86.4 89.5 91.0 Capacity retention after 200 cycles (%) 92.3 84.2 88.7 89.3 It can be seen from the test results in Table 1 that when the negative electrode material prepared in Example 1 is used in a sodium ion battery, the first discharge specific capacity is 428.9 mA·h / g, the first coulombic efficiency is 93.5%, and the capacity retention rate after 200 cycles is 92.3%. The negative electrode material of Example 1 is superior to that of Comparative Examples 1-3 in terms of the first discharge specific capacity, the first coulombic efficiency, or the capacity retention rate after cyclic use, which can illustrate that the asphalt-based sodium ion battery hard carbon negative electrode material prepared in Example 1 of the present invention not only performs well in terms of specific capacity and coulombic efficiency, but also has the advantage of a long cycle life.

[0035] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0036] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material, characterized in that: The following steps are involved: Step 1, weighing silicon powder and hafnium powder, mixing them, first ball-milling them under the protection of inert gas, and then pressing them into tablets and placing them in a graphite furnace for heating treatment to obtain hafnium silicide powder; Step 2, mixing cobalt acetate tetrahydrate, sodium selenite and deionized water, adding hafnium silicide powder, and stirring thoroughly to obtain a mixed solution A; weighing ascorbic acid and dissolving it in deionized water, stirring evenly to obtain a mixed solution B; mixing the mixed solution A and the mixed solution B, reacting in a reactor, and obtaining hafnium silicide & cobalt selenide composite microspheres after the reaction is completed; Step 3, mixing the hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt, and performing ball milling to obtain an asphalt-based mixture; Step 4, placing the asphalt-based mixture in a graphite furnace, introducing nitrogen as a protective gas, heating it, and cooling it to obtain a hard carbon negative electrode material.

2. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the step 1, the purity of the silicon powder and the hafnium powder are both greater than 99%, and the particle size is 50±5 μm; the mass ratio of the hafnium powder to the silicon powder is 1.78:0.56-0.

6.

3. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the step 1, the ball milling speed is 200-400 r / min, and the ball milling time is 5-10 h; the temperature of the graphite furnace is 900-1300° C., and the processing time is 2-5 h.

4. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the mixed solution A in step 2, the mass ratio of hafnium silicide powder, cobalt acetate tetrahydrate, sodium selenite and deionized water is 1:0.25-0.5:0.17-0.34:15-25; in the mixed solution B, the mass ratio of ascorbic acid to deionized water is 0.3-0.5:

10.

5. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In step 2, the mixed solution A and the mixed solution B are mixed in the following manner: after the mixed solution A is stirred at 50-80° C. for 2-4 hours, the mixed solution B is added dropwise, and after all the mixed solution B is added, the stirring is continued for 0.5-1 hour.

6. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the step 2, the mass ratio of the mixed solution A to the mixed solution B is 1:0.3-0.8; the temperature of the reactor is 130-180° C., and the reaction time is 5-10 h.

7. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the step 3, the mass ratio of the hafnium silicide & cobalt selenide composite microspheres, reduced graphene oxide and asphalt is 0.2-2:0.1-1:

10.

8. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In the step 3, the ball milling speed is 250-450 r / min, and the ball milling time is 3-10 h.

9. The method for preparing a pitch-based sodium ion electrode hard carbon negative electrode material according to claim 1, characterized in that: In step 4, the temperature in the graphite furnace is first raised to 250-300° C., kept warm for 1-3 hours, and then raised to 750-950° C., kept warm for 1-3 hours.

10. A pitch-based sodium ion electrode hard carbon negative electrode material prepared using the preparation method according to claim 1.

Citation Information

Cited By

  • Preparation method of nano hafnium silicide

    CN121470492A